Analisis break even point dan risiko pendapatan usahatani ikan Nila (Oreochromis niloticus) keramba jaring apung di Desa Pematang Panjang Kecamatan Seruyan Hilir Timur Kabupaten Seruyan - Lili Winarti (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
This study aims to analyze Break Even Point and income risk of Tilapia farming in floating net in Pematang Panjang Village, Subdistrict Seruyan Hilir Timur, District Seruyan. Tilapia farmers using floating net amounted to 17 people who all became respondent in this study. Data analysis used was qualitative analysis and quantitative analysis. Qualitative analysis was conducted to obtain the description of Tilapia farming and quantitative analysis to analyze Break Even Point (BEP) and income risk of farming. Based on the result of this research, Break Even Point value from production was 53.95 Kg / production and Break Even Point value from sales was Rp 1,618,357,20 per production. The average income of tilapia farming was Rp7.120.524,37. The minimum income risk that received by farmers during their farming was Rp 1,064,845,56 / kg.